2015
DOI: 10.1016/j.molp.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide: A Multitasked Signaling Gas in Plants

Abstract: Nitric oxide (NO) is a gaseous reactive oxygen species (ROS) that has evolved as a signaling hormone in many physiological processes in animals. In plants it has been demonstrated to be a crucial regulator of development, acting as a signaling molecule present at each step of the plant life cycle. NO has also been implicated as a signal in biotic and abiotic responses of plants to the environment. Remarkably, despite this plethora of effects and functional relationships, the fundamental knowledge of NO product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
243
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(261 citation statements)
references
References 182 publications
10
243
0
2
Order By: Relevance
“…Increased production of NO and/or H 2 O 2 in plants responding to abiotic stresses can cause cell death (Brüne 2003; Gao et al 2008;Breusegem and Dat 2006;Arasimowicz et al 2012;Domingos et al 2015). Our present study showed that SO 2 toxicity was decreased by scavengers of NO or H 2 O 2 and could be completely reversed when NO and H 2 O 2 scavengers were both present.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Increased production of NO and/or H 2 O 2 in plants responding to abiotic stresses can cause cell death (Brüne 2003; Gao et al 2008;Breusegem and Dat 2006;Arasimowicz et al 2012;Domingos et al 2015). Our present study showed that SO 2 toxicity was decreased by scavengers of NO or H 2 O 2 and could be completely reversed when NO and H 2 O 2 scavengers were both present.…”
Section: Discussionsupporting
confidence: 56%
“…Currently available data suggest that there are two distinct enzymatic pathways for the generation of NO in plants: the arginine-dependent NOS pathway and the nitrite-dependent NR pathway (Domingos et al 2015). In the present study, enhanced NO production is accompanied with NR activation and cell viability loss in SO 2 -treated samples, meanwhile both cell death and NO elevation induced by SO 2 can be blocked by NO scavenger c-PTIO or NR inhibitor tungstate.…”
Section: Discussionsupporting
confidence: 50%
“…NO is known to influence multiple steps during the pollen-ovary interaction, functions as a short-range guidance signal for the reorientation of pollen tubes toward ovules, and promotes further growth through the funiculus to the micropyle (for review, see Traverso et al, 2013;Domingos et al, 2015). Importantly, this involves thiol-based redox regulation, which may redirect the first two OPPP reactions from plastids to peroxisomes (Meyer et al, 2011;Hölscher et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Degu et al (2016) found that menadione exogenously applied to detached grapevine berries as an oxidative stress inducer (releases ROS such as O 2 Á-, H 2 O 2, and OḢ ), increased stilbene production levels both at pre-veraison and veraison stages. Nitric oxide (NO) is known as a gaseous ROS belonging to the subgroup of reactive nitrogen species (RNS) that is synthesized in response to pathogen attack and can promote plant defense response (Domingos et al 2015). Vandelle et al (2006) revealed that a phosphorylation-dependent NO production is involved in the activation of PAL and STS transcription in grapevine cell suspension cultures in response to treatment with the endopolygalacturonase 1 (BcPG1), a potent fungal elicitor.…”
Section: Signaling Pathways Regulating Stilbene Biosynthesis Regulatimentioning
confidence: 99%